Recetario de cócteles creativos - Orozco Sibille, Fiorella (2019)
Autores del trabajos: Michela Calda; Rosario Ramos; José Gómez; Carlos Villa; Jaqueline Pariachi; Marhorie Rojas; Anibal Vidarte; Camila Ahumada; Harim Paucas; Anny Rejas; Andres Encinas; Marco Zapata; Sheyla Saavedra; Alexander Coronado; Pedro Velasco; Ashley Pinto; Seleste Contreras; Isabel Espinoza; Fernando Viralta; Jornet Vicente; Dayanna Vigo; Ricardo Macahado; Dalia Rixe ; Mayra Jara; Any Wong; Yrene Casabona; Victor Luperdi; Santiago Nuñez; Raquel Peña; Vanessa García; Rosario Luna; Katherine Olarte; Katty Cubas; Karen Flores; Gabriela Glasinovich; Alexia Lam ; Rose Vasquez; Gianfranco Philco; Carmen Solis; Yhare Ricra; Andrea Velasque; Katheriine Barrientos; Gemma Valdivieso; Andrea Hoffman.